2019
DOI: 10.1111/pai.13098
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis – Lessons learnt when East meets West

Abstract: The rapidly increasing prevalence of allergic disorders over the past 2 decades highlights the need to understand the epidemiology of anaphylaxis. In Europe, the United States, and Australia, the incidence of anaphylaxis is estimated to be between 60 and 950 cases per 100 000 population, with a lifetime prevalence of anaphylaxis of 0.05%‐2%. The incidence appears to be increasing over time. Although the existing Asian literature is heterogeneous and limited by under‐reporting, it also suggests a similar increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 62 publications
(177 reference statements)
2
23
0
Order By: Relevance
“…In the presented material, only several percent of physicians prescribed adrenaline to a paediatric patient. It appeared to be a worldwide issue, also observed by other Polish authors with respect to venom anaphylaxis in adults [27,29]. The data summarized indicated that physicians performing first intervention presented limited familiarity with anaphylaxis, recommended management during acute symptoms and follow-up visits.…”
Section: Preventive Measures After the Episode Of Anaphylaxismentioning
confidence: 63%
“…In the presented material, only several percent of physicians prescribed adrenaline to a paediatric patient. It appeared to be a worldwide issue, also observed by other Polish authors with respect to venom anaphylaxis in adults [27,29]. The data summarized indicated that physicians performing first intervention presented limited familiarity with anaphylaxis, recommended management during acute symptoms and follow-up visits.…”
Section: Preventive Measures After the Episode Of Anaphylaxismentioning
confidence: 63%
“…The APAPARI Anaphylaxis Study Group has looked into such differences, and they present their views in the review article which opens this issue nicely. 1 They have seen an increasing trend in the prevalence of anaphylaxis over the last decades, similar to Western countries. Nevertheless, they encounter unique triggers for reactions, such as Chinese traditional medicine, or galacto-oligosaccharides (carbohydrates added to commercially available food products and beverages).…”
Section: Fecal Metabolites and Early Sensitization Influence Asthma mentioning
confidence: 99%
“…In particular, we may see differences between Asia, and Europe or North America. The APAPARI Anaphylaxis Study Group has looked into such differences, and they present their views in the review article which opens this issue nicely . They have seen an increasing trend in the prevalence of anaphylaxis over the last decades, similar to Western countries.…”
mentioning
confidence: 99%
“…IgE-mediated reactions to wheat, particularly anaphylaxis and exercise-induced anaphylaxis has been increasingly observed worldwide [1]. In Japan, wheat allergy has become the third leading cause of anaphylaxis in children following egg and cow's milk [2].…”
Section: Introductionmentioning
confidence: 99%